PERSEPSI ORANG TUA TENTANG PORNOGRAFI DAN PENGARUHNYA TERHADAP CARA MENDIDIK ANAK DI DUSUN IV DESA BANGUN SARI BARU KECAMATAN TANJUNG MORAWA - Khairuddin YM; Ahmad Fuadi (Politeknik Negeri Sriwijaya, 2018)
Rapid technology and information advancements significantly improve human lives. People's lives have been made easier by technical advances such as the internet, smartphones, TV, and electricity. This is alarming because it can harm poverty patterns and children's conduct, determining the nation's destiny. Experts convene to devise a